Evolutionary origin of a periodical mass‐flowering plant - Kakishima, Satoshi (Ecol Evol, 2019)
The evolutionary origin of periodical mass‐flowering plants (shortly periodical plants), exhibiting periodical mass flowering and death immediately after flowering, has not been demonstrated. Within the genus Strobilanthes (Acanthaceae), which includes more than 50 periodical species, Strobilanthes flexicaulis on Okinawa Island, Japan, flowers gregariously every 6 years. We investigated the life history of S. flexicaulis in other regions and that of closely related species together with their molecular phylogeny to reveal the evolutionary origin of periodical mass flowering. S. flexicaulis on Taiwan Island was found to be a polycarpic perennial with no mass flowering and, in the Yaeyama Islands, Japan, a monocarpic perennial with no mass flowering. Molecular phylogenetic analyses indicated that a polycarpic perennial was the ancestral state in this whole group including S. flexicaulis and the closely related species. No distinctive genetic differentiation was found in S. flexicaulis among all three life histories (polycarpic perennial, monocarpic perennial, and periodical plant). These results suggest that among S. flexicaulis, the periodical mass flowering on Okinawa Island had evolved from the polycarpic perennial on Taiwan Island via the monocarpic perennial in the Yaeyama Islands. Thus, the evolution of life histories could have taken at the level of local populations within a species.